Self-perceptions, perceived control and anxiety in children and adolescents at risk of developmental coordination disorder. - Skinner, Rosemary (Curtin University, 2002)
The current study aimed to discover whether, and to what extent, children and adolescents at risk of Developmental Coordination Disorder (DCD) perceive themselves as lacking competence, control, social support and self-worth. In addition, the study aimed to discover whether, and to what extent, children and adolescents at risk of DCD experience more trait and state anxiety than their peers. Fifty-eight children aged 8- to 10-years identified as being at risk of DCD were matched with 58 control children on age and gender, and fifty-one adolescents aged 12- to 14-years at risk of DCD group were matched with 51 control adolescents. Children and adolescent at risk of DCD were compared to the control group on measures of perceived competence, perceived control, perceived social support, self-worth and anxiety. Multivariate Analysis of Variance revealed that children and adolescents at risk of DCD performed significantly more poorly than the control group on measures of perceived competence, perceived control, perceived social support, self-worth and state and trait anxiety. In addition, significant differences were found on some measures for age, whilst only the self-perception profile differentiated gender.Based on the assumption that children and adolescents with poor motor coordination do have negative views of self and experience relatively high levels of anxiety, a second aim of the study was to test an aetiological model of anxiety. Harters (1987) model of the determinants of self-worth provided a sound theoretical basis for investigating the relationships between self-perceptions and affect. Self-perception, according to Harter, precedes emotional and behavioural outcomes. A series of path analyses conducted separately for each group revealed differences in the pattern of interrelationships between the dependent variables for children and adolescents at risk of DCD and the control group. The salient findings were that for both groups physical appearance was an important and consistent determinant of self-worth. Few significant pathways were identified for those in the DCD group limiting the conclusions that could be drawn from this study.Overall, given the negative consequences of poor motor coordination identified in the current study it would seem imperative that early assessment and diagnosis of DCD be introduced into the school system.